Color and Glossiness Properties of Wood Material Surfaces Coated with Aloe Vera Doped Varnish - Ahmet Cihangir Yalinkilic (BioResources)
Surface properties of wood materials were determined before and after coating with cellulosic varnish doped with aloe vera gel. For this purpose, samples were prepared from Anatolian black pine (Pinus nigra subsp. pallasiana), fir (Abies nordmanniana subsp. bornmulleriana Mattf.), Ayous (Triplochiton scleroxylon K. Schum), and Scotch pine (Pinus sylvestris L.) woods in accordance with TS 53 (1981) and TS ISO 3129 (2021) principles and then coated with cellulosic varnishes doped with 0%, 5%, 10% and 15% aloe vera (L.) gel according to ASTM D3023-98 (2017) principles. Color changes according to ASTM D2244-21 (2021) and surface glosses according to TS EN ISO 2813 (2014) were determined on varnished surfaces. As the percentage of aloe vera gel in the varnish increased, the red color tone, yellow color tone, total color change, glossiness perpendicular and parallel to the fibers, and difference values decreased. Aloe vera gel can be preferred as an additive in cellulosic varnish in applications where the objective is no change or minimal change in the color and glossiness values, depending on type of wood and area of use.